Accuracy of Urologic Conditions Portrayed on Grey's Anatomy. (April 2022) - Zhao, Hanson; Anger, Jennifer T.
Despite the common prevalence of urologic diseases, studies have demonstrated that the general public often has little knowledge or insight into the field of urology or the role of an urologist. In this study, we investigated the context, frequency, and accuracy of urologic conditions on the television series Grey's Anatomy . We reviewed episodes from the first 15 seasons. Episodes with urologic references were then screened and the urologic conditions, outcomes, and treatments were recorded. We identified a total of only 21 urologic events across 15 seasons and 342 episodes of Grey's Anatomy . A total of 52% (11/21) of the conditions were related to external male genitalia. The portrayal of these conditions and the associated treatments were considered to be medically accurate within reason 62% (13/21) of the time. There is significant room for improvement to increase the portrayal of common urologic conditions and malignancies to improve the public's awareness and perception of our specialty.